Polbeng Business Expo Chapter II: Case Study at Warung Nongkrong Pajero and Kue Donat Varian Rasa Azkia MSMEs - Rizki Saputra; Yunelly Asra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine the role of Polbeng Business Expo Chapter II in encouraging the development of Micro, Small, and Medium Enterprises (MSMEs), with case studies of Warung Nongkrong Pajero and Kue Donat Varian Rasa Azkia. This project focused on improving marketing, digitalization, financial management, and the implementation of business governance practices through direct involvement in exhibition activities. The method applied was a project-based approach, which included the stages of planning, implementation, completion, and reporting. Data collection was carried out through direct observation, documentation, and financial recording during the exhibition. The implementation of this project included compiling MSME profiles, creating promotional catalogs, marketing videos, digital marketing content, providing a QRIS-based digital payment system, and preparing financial reports. The project results showed that participation in Polbeng Business Expo Chapter II had a positive impact on the progress of both MSMEs. Digital marketing and promotion strategies were proven successful in increasing product visibility and consumer interest, as indicated by higher sales figures during the exhibition compared to regular operating days. The implementation of the QRIS system was able to improve transaction efficiency and support more organized financial governance. Furthermore, financial analysis shows that both MSMEs achieved positive net profits and recorded capital growth, indicating healthy and sustainable business performance. In addition to generating economic benefits, this project also provided educational value for students through the practical application of business theory, as well as strengthening synergies between higher education institutions, MSMEs, and the community. Overall, Polbeng Business Expo Chapter II proved to be an effective platform for MSME escalation through integrated marketing, digitalization, and financial management support.